Development of the Android-based "Misi Gimako" Game as a Class High School Learning Media: Pengembangan Game “Misi Gimako” Berbasis Android Sebagai Media Pembelajaran SMA - Sofi, Angelia; Hasanah, Fitria Nur (Inquest Journal, 2023)
This research explores the potential of Android-based educational games in enhancing learning experiences for high school students, focusing on informatics subjects. Employing the ADDIE development model—comprising Analysis, Design, Develop, Implement, and Evaluate—the study aims to assess the efficacy of these games as learning media. Research involves 10 randomly selected students, evaluating both randomly chosen and expert-validated educational games. Utilizing the Cocket as the research instrument, the findings aim to bridge existing knowledge gaps in educational technology, offering insights into optimizing technology for educational purposes.